Enhancing the use of coal-fly ash in coarse aggregates concrete. (2020) - Shanmugan, S.; Deepak, V.; Nagaraj, J.; Jangir, Deepak; Viyagula Jegan, S.; Palani, S.
Abstract: The experimental work has been made to estimate the operation of coal-fly ash as acceptable and coarse aggregates concrete with the ordinary Portland cement of 53 grade. Initially, the chemical and physical characteristics of coal-fly ash particles, such as chemical compositions, detailed significance and XRD, SEM images have been studied. The effect of acceptable to the coal-fly ash on the movement characteristics of palletisation process have been studied in form of particle and cement absorption of coal-fly ash. Additionally, the experimental is showed by substituting acceptable and is constituents with preparation of cement & Fly ash ratio on 20:80, water binder ratio: 0.3 with effect of experienced at 32 days. The properties of fly ash coarse aggregates (FCA) were experimental studied if only based on the aggregate soundness test, crushing value, impact value, abrasion value and water absorption. The impact value test analysis of their two synthesis like as (i) fly ash coarse aggregate concrete (FAC-100%FCA) (ii) Conventional coarse aggregate (CC-100%CA) and partially replaced fly ash coarse aggregate concrete (PRFAC − 50%CA + 50%FCA) to verified in IS methods of M30 grade and its good fitness of microanalysis. To compare the influence of FACA concrete is exposed to that use of fly ash slightly touches the permanence (Fresh, hardened and durability) properties of conventional concrete.